ARTool Zero: Programming trajectory of touching probes using augmented reality. (October 2018) - Ragni, Matteo; Perini, Matteo; Setti, Amedeo; Bosetti, Paolo
Highlights: An Augmented Reality interface for programming movements of touching probe is proposed. Geometrical features are used for 3-D location of keypoints. System interfaces are abstracted as API. A practical implementation of the application is shown An example of real usage of the proposed system is shown Abstract: In manufacturing applications, process preparation is a time consuming and an error prone operation, and costs are especially relevant when dealing with small batches. One mandatory operation for machining preparation is the raw material alignment with respect to machine reference frame, commonly done through an electronic touching probe. Machine manufacturers implement in-controller preparatory codes for the identification of a range of geometric features (simple contacts, plane normals, circles, etc.) in order to make alignments faster, but those procedures rely on human-input parameters, and an error may have catastrophic consequences for the probe itself. ARTool Zero supports the operators in programming touching probe trajectories, generating and simulating on-the-fly the part-program that guides the probe in the identification of a geometric features. The interface of ARTool Zero is an augmented reality application based on the ARTool Framework. The application runs on a mobile device that communicates with the machine controller. ARTool Zero projects coordinates from the mobile device screen to the machine active reference frame through the means of markers. One of the markers acts as an anchor for a virtual plane, i.e. the plane in the real world on which the mobile screen coordinates are projected, allowing to convert a 2D screen tap in a 3D point in space. Ego-localization accuracy is one of the critical aspects of the application, thus the validation of the core ARTool library is discussed. A video that presents the application in a real-case scenario is available athttps://youtu.be/wFF89pqfm6c .